Efficacy and safety of pembrolizumab as first-line treatment for advanced non-small cell lung cancer complicated with chronic obstructive pulmonary disease: protocol for a prospective, single-arm, single-center, phase II clinical trial - Dong, Weigang; Yin, Yan; Liu, Bin; Jiang, Yan; Wang, Lei; Shi, Dongsheng; Qin, Jianwen (Frontiers in Oncology, 2024)
Background: The first-line standard treatment option for patients with NSCLC complicated with Chronic obstructive pulmonary disease (COPD) is still unclear and relies on the treatment option of NSCLC alone. To date, a limited number of retrospective studies have explored the efficacy and safety of immunotherapy in patients with NSCLC complicated with COPD. We therefore designed this study to further explore the efficacy and safety of first-line immunotherapy in patients with NSCLC complicated with COPD. Methods: This study was designed as a single-armed, single-center, prospective, phase II clinical study. It will include 30 advanced (stage IV) NSCLC combined with COPD primary treatment subjects. Each subject’s diagnosis will be confirmed by clinical, radiographic, pathologic, and pulmonary function evaluation. A fixed dose of 200 mg pembrolizumab will be administered by intravenous infusion on day1 every 3 weeks (Q3W). The management of stable and acute exacerbations of COPD include home oxygen therapy, and the use of conventional medications are also administered. Imaging evaluation will be performed every 6 weeks for 6 months from the first pembrolizumab dose and approximately every 12 weeks thereafter until disease progression or early withdrawal. COPD status will be evaluated every 3 months by pulmonary function, GOLD grading, mMRC score, CAT score, ABCD grouping, and AECOPD severity. The primary outcome is Progression-free survival. The secondary outcome measures include objective response rate, overall survival, rate of acute exacerbations of COPD (times/year), lung function, mMRC score, CAT score, impact of treatment on patient’s health-related quality of life, antibiotic use (including duration and classes), and adverse events associated with immune checkpoint inhibitors. Exploratory endpoint is to explore the association between COPD grade and the degree of immune cell (CD4+ T lymphocytes and CD8+ T lymphocytes) infiltration, as well as the association between COPD grade and the efficacy of immune checkpoint inhibitors.